QUANTIFICATION OF ATROPINE IN LEAVES OF ATROPA BELLADONNA: DEVELOPMENT AND VALIDATION OF METHOD BY HIGH-PERFOMANCE LIQUID CHROMATOGRAPHY (HPLC) - Mariana Koetz; Thalita Gilda Santos; Magda Rayane; Amélia Teresinha Henriques (Drug Analytical Research, 2017)
The leaves of Atropa belladonna (L) are characterized by the presence of the alkaloid atropine, known for the antimuscarinic activity. The leaves are used in therapy, mainly  in homeopathic preparations. An HPLC method was developed and validated to quantify atropine in belladonna leaves. The samples were extracted with methanol, followed by acid-base extraction with 5% HCl and dichloromethane. Analysis by HPLC was performed on C18 column, in a linear gradient system using a system with two mobile phases (water and acetonitrile), both acidified with trifluoroacetic acid. The determinations were performed using a reference standard and a diode array detector at 210 nm. The method was validated and proved to be specific / selective, comparing the UV profiles and the purity of the atropine peaks in reference and sample solutions and analyzing sample solutions with and without addition of standard, which produced an increase only of the area of peak of the sample, without changing the area of the adjacent peaks. The linearity (50 - 200 μg/mL) was provided by analysis of the analytical curves of atropine, with r2 = 0.9996. LOD and LOQ were 3.75 and 11.4 µg/ml, respectively. The method was precise, reproducible and accurate, and presented recovery equal to 103.0%. The method was considered robust for the analyzed parameters. Four commercial samples were analyzed and the mean levels of atropine found ranged from 0.16 - 0.27 %. Thus, the developed method is effective for quantification of atropine in beladona leaves and meets the validation requirements of current legislation and ensuring the quality control of the plant material.